Correlation between the microstructure and corrosion behaviour of copper/316 L stainless-steel dissimilar-metal welded joints. (October 2021) - Xu, Youwei; Hou, Xuqian; Shi, Yu; Zhang, Wenzhu; Gu, Yufen; Feng, Changgen; Volodymyr, Korzhyk
Highlights: Microstructure–corrosion behavior correlation investigated. Phase separation occurs in Cu/steel welded joints. There are multiple corrosion galvanic couples in Cu/steel welded joints. Joints failed at the Cu side of the interface between the Cu- and Fe-rich regions. Abstract: In this study, the correlation between the microstructure and corrosion behaviour of copper/316 L stainless-steel dissimilar-metal welded joints on an electrolytic copper cathode plate was experimentally investigated. Clear phase separation was noted in the weld metal with the γ- and ε-Cu phase dominating the Fe-rich and Cu-rich zones, respectively. The difference in the corrosion resistance of these zones means that multiple galvanic corrosion couples are formed in different joint areas. Strong galvanic corrosion between the γ and ε-Cu phases caused the shedding of the γ phase particles from the surface, thereby producing corrosion pits and eventually leading to joint failure.